Organizações internacionais não governamentais e as migrações internacionais: um estudo sobre os migrantes por sobrevivência salvadorenhos - Silva Neto, Aluizio Pessoa da (2022)
The historical construction of El Salvador was marked by different expressions of violence. Among these, armed social violence is currently one of the main challenges faced by the country. Consequently, forced migration here referred to as survival migration, has been the only alternative for Salvadorans who no longer feel safe. In this scenario, international non-governmental organizations, including humanitarian aid organizations, have been working to support this population under the circumstances of migration caused by violence. Thus, the present study starts from the following question: how does the participation of international non-governmental humanitarian aid organizations occur in the governance of migrations caused by armed social violence in El Salvador? To answer the question, a case study on the organizations Médecins Sans Frontières, the International Committee of the Red Cross, and Caritas of El Salvador is carried out. The research is characterized as exploratory-descriptive and has a qualitative approach. As data collection techniques, semi-structured interviews and documental and bibliographic research are used. Among other points, the study concludes that besides developing fieldwork focused on the guarantee of the rights of survival migrants, the organizations studied contribute by spotlighting the issue to other national and international actors. In addition, among the challenges faced by these organizations and identified in the study, budgetary issues and the confrontation with armed social violence when carrying out their activities stand out.